Quand "la maison signifiait quelque chose": la famille selon l'École sociale populaire, 1918-1939 - Quesney, Chantale (Histoire sociale / Social History, 2002)
Keywords: Famille; École Sociale Populaire

Residential Segregation of Visible Minorities in Canada's Gateway Cities - Bauder, Harald; Sharpe, Bob (The Canadian Geographer / Le Géographe canadien, 2002)
Keywords: Logement

Le versant canadien-français de la génération « non-conformiste » européenne des années trente: la revue La Relève - Angers-Fabre, Stéphanie (Recherches sociographiques, 2002)
Keywords: Relève (La)

Designing for "the Little Convalescents" Children's Hospitals in Toronto and Montreal, 1875-2006 - Adams, Annmarie; David, Theodore (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2002)
Keywords: Enfants; Hôpitaux

Food for Thought: Community Supported Agriculture and Learning - Ambach, Michael (Université Concordia, 2002)
Keywords: Jardins

La propriété et le travail: l’enracinement des Portugais sur la Main - Andrade, Miguel Simão (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Portugais; Travail

La division de l'espace résidentiel montréalais en fonction de la langue maternelle: apport des indices de ségrégation - Apparicio, Philippe; Séguin, Anne-Marie (Canadian Journal of Urban Research / Revue canadienne de recherche urbaine, 2002)
Keywords: Francophones

Le Domaine. Une belle histoire qui se poursuit... Les jardins du Domaine - Archambault-Malouin, Diane (Les Services du Domaine Inc, 2002)
Keywords: Domaine Saint-Sulpice; Jardins

Beyond Romance: Courtship and Marriage in Montreal between the Wars - Baillargeon, Denyse (Rethinking Canada History. The Promise of Women's History, 2002)
Keywords: Mariage

Care of Mothers and Infants in Montreal between the Wars: the Visiting Nurses of the Metropolitan Life Milk Deposits and Assistance maternelle - Baillargeon, Denyse (Quebec since 1800: Selected Readings, 2002)
Keywords: Assistance maternelle; Goutte de lait; Infirmières

Entre la "Revanche" et la "Veillée" des berceaux: les médecins québécois francophones, la mortalité infantile et la question nationale, 1910-1940 - Baillargeon, Denyse (Revue d'histoire sur l'éducation / Historical Studies in Education, 2002)
Keywords: Enfants; Francophones; Mortalité; Médecine; Nationalisme

Indispensable but not a Citizen: the Housewife in the Great Depression - Baillargeon, Denyse (Contesting Canadian Citizenship. Historical Readings, 2002)
Keywords: Crise; Famille; Femmes

Les Gouttes de lait de Montréal. Une institution médicale aux multiples usages - Baillargeon, Denyse (Espaces et temps de la maternité, 2002)
Keywords: Femmes; Goutte de lait; Hôpital Sainte-Justine

Acculturation et santé mentale: stress psychologique et satisfaction maritale chez des couples immigrants marocains à Montréal - Barampama, Mireille (Université de Montréal, 2002)
Keywords: Maghrébins; Marocains

H.-A. Verreau, ptre (1828-1901). Deuxième président de la Société historique de Montréal - Beaudoin, Léo (Montréal en tête, 2002)
Keywords: Chauveau, Pierre-Joseph-Olivier; Communautés religieuses; Histoire; Historiens; Société historique de Montréal; École normale Jacques-Cartier; Écoles normales

L'immigration kabyle à Montréal: vivre sa berbérité au Québec - Beaumont, Valérie (Université de Montréal, 2002)
Keywords: Maghrébins

Communalisations ethniques post-migratoires: le cas des Turcs de Montréal - Bilge, Sirma (Université Sorbonne Nouvelle - Paris 3, 2002)
Keywords: Turcs

Re-Thinking Rites of Passage in Contemporary Double-Ring Ceremonies in Montreal Jewish Weddings - Bonneau, Marlene (Université Concordia, 2002)
Keywords: Juifs; Mariage

Mouvements sociaux et économie sociale: un arrimage en constante reconstruction - Boucher, Jacques L. (Économie et solidarités, 2002)

Women’s Workplaces: The Impact of Technological Change on Working-Class Women in the Home and in the Workplace in Nineteenth Century Montreal - Bradbury, Bettina (Rethinking Canada. The Promise of Women’s History, 2002)
Keywords: Femmes; Travail

La prise en charge pénale des personnes itinérantes: analyse de dossiers policiers - Campeau, Paule (Université du Québec à Montréal, 2002)
Keywords: Itinérance; Police

Le déclin de la maison de fond de cour à Montréal, 1880–1920 - Carey, Luc (Urban History Review / Revue d'histoire urbaine, 2002)
Keywords: Logement

Folie, internement et érosion des solidarités familiales au Québec: une analyse quantitative - Cellard, André (Bulletin d'histoire politique, 2002)
Keywords: Famille; Hôpitaux; Hôpitaux psychiatriques

Les banlieues de l’immigration - Charbonneau, J; Germain, Annick (Recherches sociographiques, 2002)

Les sciences infirmières: genèse d’une discipline: histoire de la Faculté des sciences infirmières de l'Université de Montréal - Cohen, Yolande; Pépin, Jacinthe; Lamontagne, Esther; Duquette, André (Presses de l'Université de Montréal, 2002)
Keywords: Infirmières; Université de Montréal

La bataille du lait pur à Montréal, 1900-1926 - Colas, Valéry (Université du Québec à Montréal, 2002)
Keywords: Alimentation

La crise, les écoliers et l’accès au lait - Colas, Valéry (Cap-aux-Diamants, 2002)
Keywords: Alimentation; Crise; Enfants

Un enjeu politique: la pasteurisation - Colas, Valéry (Cap-aux-Diamants, 2002)
Keywords: Alimentation; Maires; Martin, Médéric

Reconstruction identitaire des jeunes en contexte migratoire: cas des jeunes québécois d'origine haïtienne - Craan, George-Marie (Université du Québec à Montréal, 2002)
Keywords: Haïtiens

L’héritage de l’Institut du Baron Hirsch: entre la commission protestante et l’école Peretz (1880-1920) - Croteau, Jean-Philippe (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Baron de Hirsch Institute; Bureau des écoles protestantes; Juifs; Protestants

L’intégration scolaire des Juifs francophones et le Bulletin du Cercle juif (1954-1968) - Croteau, Jean-Philippe (Bulletin d'histoire politique, 2002)
Keywords: Francophones; Juifs

Les communautés religieuses de Montréal. Tome 2: Les communautés religieuses et l'éducation à Montréal, 1657-1900 - D'allaire, Micheline (Cursus universitaire, 2002)
Keywords: Communautés religieuses; Enseignants

La mixité sociale en habitation - Dansereau, Francine; Charbonneau, Stéphane; Morin, Richard; Révillard, Anne; Rose, Damaris; Séguin, Anne-Marie (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2002)

Fin ou renaissance des quartiers? Les significations des territoires de proximité dans une ville pluriethnique - Dansereau, Francine; Germain, Annick (Espaces et Sociétés, 2002)
Keywords: Quartiers

L’Église catholique du Québec et "l’épreuve" de la Révolution tranquille. Première partie: la condamnation du Frère Untel - Dassylva, Martial (Bulletin d'histoire politique, 2002)
Keywords: Langue

Une communauté en transition: la Petite Italie de Montréal - Del Balso, Michael (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Le secours mutuel en transformation: l'Alliance nationale (1892-1948) - Desaulniers, Annie (Université du Québec à Trois-Rivières, 2002)
Keywords: Assurance

Restauration de l’église St. James: laboratoire de savoir-faire - Descôteaux, Josée (Continuité, 2002)
Keywords: Conservation; Églises

Guerre aux bactéries - Dubé, Thaïs (Cap-aux-Diamants, 2002)
Keywords: Enfants; Lait; Mortalité

Ensemble se donner une voix pour mieux être, 1977-2002: histoire du Front commun des personnes assistées sociales du Québec - Dumas, Evelyn (Front commun des personnes assistées sociales du Québec, 2002)
Keywords: Groupes populaires; Pauvreté

Les modèles implicites d'intervention en médiation interculturelle: le cas de médiatrices interculturelles dans des organismes communautaires francophones à Montréal - El-Hage, Habib (Université du Québec à Montréal, 2002)

Counting the Costs of Living: Gender, Citizenship, and a Politic of Price in 1940s Montreal - Fahrni, Magda (Canadian Historical Review, 2002)
Keywords: Alimentation; Femmes; Prix; Épicerie

Trajectoires migratoires et espaces de sociabilité: stratégies de migrants de France à Montréal - Fortin, Sylvie (Université de Montréal, 2002)
Keywords: Français

Soigner le corps et l'âme : les Hospitalières de Saint-Joseph et l'Hôtel-Dieu de Montréal, XVIIe-XXe siècles - Gagnon, Hervé (Éditions GGC, 2002)
Keywords: Communautés religieuses; Hospitalières de Saint-Joseph; Hôpitaux; Hôtel-Dieu

Espace urbain et religion: esquisse d’une géographie des lieux de culte minoritaires de la région de Montréal - Gagnon, Julie Élizabeth; Germain, Annick (Cahiers de géographie du Québec, 2002)
Keywords: Juifs; Maghrébins

Histoire du Service de santé de la ville de Montréal, 1865-1975 - Gaumer, Benoît; Desrosiers, Georges; Keel, Othmar (Culture et société, 2002)
Keywords: Fonctionnaires

La culture urbaine au pluriel? Métropole et ethnicité - Germain, Annick (Traité de la culture. Le Québec, son patrimoine, ses modes de vie et ses productions culturelles, 2002)
Keywords: Métropole

Trente ans d'écrits syndicaux: contributions à l'histoire du SPUQ - Gill, Louis (Syndicat des professeurs et professeures de l'Université du Québec à Montréal, 2002)
Keywords: Enseignants; Université du Québec à Montréal

L'influence des caractéristiques liées à l'entreprise et aux travailleurs sur l'usage prédominant du français dans les petites manufactures de la région de Montréal - Girard-Lamoureux, Catherine (Université de Montréal, 2002)

Éduquer et vendre: la Santé par le Lait Inc. - Giroux, Éric (Cap-aux-Diamants, 2002)
Keywords: Lait

Four Hundred Brothers and Sisters: Two Jewish Orphanages in Montreal, Quebec, 1909-1942 - Gordon, Judy (Lugus, 2002)
Keywords: Enfants; Juifs; Orphelinats

Vers l’avenir. Québec Women’s Politics Between 1945 and 1967: Feminist, Maternalist and Nationalist Links - Gosselin, Cheryl A. (Université de Montréal, 2002)
Keywords: Femmes; Féminisme; Nationalisme

La médecine légale des aliénés selon Georges Villeneuve (1895-1917) - Grenier, Guy (Bulletin d'histoire politique, 2002)
Keywords: Hôpital Saint-Jean-de-Dieu; Hôpitaux psychiatriques; Médecine

Histoire de l'École des Hautes études commerciales de Montréal. Tome 2: 1926-1970 - Harvey, Pierre (Québec Amérique, 2002)
Keywords: École des hautes études commerciales

A Maternalist Organization in Quebec: The Fédération Nationale Saint-Jean-Baptiste and the Struggle for Women’s Suffrage - Hébert, Karine (Quebec since 1800: Selected Readings, 2002)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

La construction d'une identité étudiante montréalaise (1895-1960) - Hébert, Karine (Université du Québec à Montréal, 2002)
Keywords: Université McGill; Université de Montréal; Étudiants

La question linguistique et le statut des allophones et des anglophones au Québec - Helly, Denise (Revue d’aménagement linguistique, 2002)
Keywords: Anglophones; Francophones; Langue

Race, classe, genre: le discours et les pratiques du milieu communautaire vis-à-vis des femmes monoparentales haïtiennes de Montréal - Henry, Irvine (Université de Montréal, 2002)
Keywords: Femmes; Haïtiens

Facteurs déterminants des styles parentaux des mères haïtiennes immigrantes à Montréal - Jean-Baptiste, Larissa (Université de Montréal, 2002)
Keywords: Famille; Femmes; Haïtiens

Les Juifs de Montréal : trois siècles de parcours exceptionnels - King, Joe (Carte blanche, 2002)
Keywords: Juifs

''Don't Let Your Girlfriends Ruin Your Marriage'': Lesbian Imagery in Chatelaine Magazine, 1950-1969 - Korinek, Valerie Joyce (Rethinking Canada History. The Promise of Women's History, 2002)
Keywords: Femmes; Mariage

Soins du corps, santé publique et moralité: les bains publics de Montréal - Labonne, Paul (Cap-aux-Diamants, 2002)

Les transformations identitaires de femmes immigrantes indiennes de religion hindoue vivant à Montréal - Ladouceur, Nadya (Université du Québec à Montréal, 2002)
Keywords: Femmes; Indiens

Histoire de l'Institut Bruchési et son engagement dans la lutte contre la tuberculose à Montréal (1911-1945) - Lajoie, Yves (Université de Montréal, 2002)
Keywords: Tuberculose

L’apport des communautés culturelles - Landry, Guy; Potvin, Nathalie (Cap-aux-Diamants, 2002)
Keywords: Patrimoine

La participation des femmes au processus de migration transnationale familiale: le cas des Shi'ites libanais à Montréal - Le Gall, Josiane (Université de Montréal, 2002)
Keywords: Famille; Femmes; Libanais

Nouveaux arrivants de 1989, langue et mobilité professionnelle sur le marché du travail de Montréal: une approche longitudinale - Lebeau, Ronald; Renaud, Jean (Cahiers québécois de démographie, 2002)
Keywords: Langue; Travail

Itinéraires identitaires chez des immigrants libanais de Montréal: le cas de l'identité confessionnelle - Lebnan, Karim (Université de Montréal, 2002)
Keywords: Libanais

Le regard des petits propriétaires sur les demandeurs de logement. Étude exploratoire sur les perceptions et les attitudes des petits propriétaires envers les clientèles des minorités ethnoculturelles. - Ledoyen, Alberte (Immigration et Métropoles, 2002)
Keywords: Locataires; Logement

L’institution ecclésiale et les structures de l’idéologie chrétienne dans les radioromans et les dramatisations historiques (1935-1975) - Legris, Renée (Études d'histoire religieuse, 2002)
Keywords: Radio; Roman

Les squeegees du centre-ville de Montréal: en quête de reconnaissance sociale et d'estime de soi - Lemetayer, Fanny (Université du Québec à Montréal, 2002)

Making and Breaking Bread in Jewish Montreal, 1920-1940 - Lerner, Eve (Université Concordia, 2002)
Keywords: Alimentation; Boulangerie; Juifs

Anniversaires et manifestations des camarades. La culture internationale et l’identitaire communistes au Canada pendant l’entre-deux-guerres - Lévesque, Andrée (Labour / Le travail, 2002)
Keywords: Communistes

Mères célibataires et infanticides à Montréal 1914-1930 - Lévesque, Andrée (Femmes et justice pénale: XIXe-XXe siècle, 2002)
Keywords: Enfants; Femmes

Entre praticiens et chercheurs: une histoire des psychologues au Canada, 1939-1971 - Marchand, Nicolas (Université du Québec à Montréal, 2002)
Keywords: Psychologie

La question linguistique dans la pensée de Claude Ryan au Devoir (1962-1978): la difficile conciliation de principes nationalistes et libéraux - Marcil, Olivier (Mens, 2002)
Keywords: Anglophones; Devoir (Le); Francophones; Langue; Ryan, Claude

La raison et l'équilibre: libéralisme, nationalisme et catholicisme dans la pensée de Claude Ryan au Devoir, 1962-1978 - Marcil, Olivier (Varia, 2002)
Keywords: Devoir (Le); Idéologies; Libéralisme; Nationalisme; Ryan, Claude

Le lock-out de La Presse et l'émeute du 29 octobre 1971: un conflit d'envergure nationale - Ménard, Yves (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Presse (La); Émeutes

Prédication et média de masse: quand le sermon devient thérapie. Portrait de l'œuvre du dominicain Marcel-Marie Desmarais - Meunier, E. -Martin (Études d'histoire religieuse, 2002)
Keywords: CKAC; Radio

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

Cinquante ans d’émissions religieuses à la radio québécoise (1931-1983). De l’apologétique au dialogue avec les grandes - Pagé, Pierre (Études d'histoire religieuse, 2002)
Keywords: Radio

Assessing Student Satisfaction and Need Levels: A Study of Concordia University's Undergraduate Student Population - Paulauskas, Louise (Université Concordia, 2002)
Keywords: Université Concordia; Étudiants

"La riante bannière de la démocratie": les sociétés de secours mutuels québécoises au 20e siècle - Petitclerc, Martin (Assurances, 2002)
Keywords: Assurance; Travail

La solidarité face au marché. Quelques réflexions sur l‘histoire de la mutualité au Québec - Petitclerc, Martin (Revue internationale de l'économie sociale, 2002)
Keywords: Assurance; Banques; Pauvreté; Union Saint-Joseph

Imperialist Intent - Colonial Response : The Art Collection and Cultural Milieu of Lord Strathcona in Nineteenth-Century Montreal - Pierce, Alexandria (Université McGill, 2002)
Keywords: Smith, Donald

La Société Saint-Vincent de Paul de Montréal et la Fédération des Oeuvres de Charité canadiennes françaises (1933-1937) - Pincemail, Véronique (Université d'Angers, 2002)
Keywords: Fédération des œuvres de charités canadiennes-françaises (FOCCF); Saint-Vincent-de-Paul (Société)

Notes préliminaires sur le rôle des intervenants psychiatriques et psychologiques à la Cour des jeunes délinquants à Montréal, 1912-1949 - Quevillon, Lucie (Bulletin d'histoire politique, 2002)
Keywords: Délinquance; Enfants; Psychologie; Tribunaux

La sociabilité littéraire au Québec: de l’usage public de la raison à la reconnaissance d’une légitimité fondée sur un principe de compétence - Rajotte, Pierre (Voix et Images, 2002)
Keywords: Clubs; Journalistes; Écrivains

Église Orthodoxe Roumaine de l'Annonciation: 8080, rue Christophe-Colomb, Montréal (Québec) Canada: étude architecturale - Rak, Valeria-Sabina (Université Concordia, 2002)
Keywords: Roumains; Églises

La violence dans le milieu communautaire des immigrants juifs montréalais - Robinson, Ira (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Idéologies; Juifs

The Church in the World: From the Malvern Conference in Britain to the Anglican Outlook and News Digest in Canada - Rogers, Linden (Université Concordia, 2002)
Keywords: Anglicans; Protestants

Le néo-chamanisme en contexte montréalais - Savard, Marcel (Université de Montréal, 2002)

Migrations et relations ethniques - Taschereau, Sylvie (Traité de la culture. Le Québec, son patrimoine, ses modes de vie et ses productions culturelles, 2002)

Tel-Aide Montréal : trente ans à l'écoute - Tel-Aide Montréal (Tel-Aide Montréal, 2002)
Keywords: Téléphone

Le regroupement culturel des Latino-Américains à Montréal - Thibeault, Frédéric (Université du Québec à Montréal, 2002)
Keywords: Latino-Américains

Derrière les murs de Saint-Jean-de-Dieu, fin XIXe début XXe siècles: illusion et désillusion - Thifault, Marie-Claude (Bulletin d'histoire politique, 2002)
Keywords: Hôpital Saint-Jean-de-Dieu; Hôpitaux psychiatriques

Un pour tous. Les aspirations démocratiques des leaders étudiants de l'Association générale des étudiants de l'Université de Montréal, 1958-1969 - Thomas, Karl-Xavier (Université du Québec à Trois-Rivières, 2002)
Keywords: Association générale des étudiants de l'Université de Montréal; Associations étudiantes; Université de Montréal

Travail et syndicalisme: naissance et évolution d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 2002)
Keywords: Travail

Fécondité différentielle des immigrants et des natifs: Québec, 1976-1996 - Tossou, Ayéko A. (Cahiers québécois de démographie, 2002)
Keywords: Fécondité

Les tribulations d'André Dagenais - Trépanier, Pierre (Les Cahiers des dix, 2002)

Protestant Restructuring in the Canadian City: Church and Mission in the Industrial Working-Class District of Griffintown, Montreal - Trigger, Rosalyn (Urban History Review / Revue d'histoire urbaine, 2002)
Keywords: Anglicans; Griffintown; Presbytériens; Protestants; Églises

Quelle mobilité? Contribution à une meilleure compréhension du phénomène social de l'itinérance - Ungureanu, Ernest (Université de Montréal, 2002)
Keywords: Itinérance

L’immigration féminine au Canada durant les années 1920: la mise en place d’une politique fondée sur le "genre" - Vallée, Marie-Hélène (Recherches féministes, 2002)
Keywords: Britanniques; Femmes

Les églises: lieux de culte et de culture - Vanlaethem, France (Montréal, la ville aux cent clochers. Regards des Montréalais sur leurs lieux de culte, 2002)
Keywords: Arts sacrés; Patrimoine; Sculpture; Vêtements; Églises

Pouvoir des enseignants: réalité ou chimère?: étude de cas d'un cégep en région urbaine - Veillette, Sébastien (Université de Montréal, 2002)
Keywords: Cégep

La professionnalisation de la Sûreté provinciale du Québec, 1960-1970 - Vézina, Jacques (Université du Québec à Trois-Rivières, 2002)
Keywords: Police

De l’École Gamelin à Rivière-des-Prairies: peut-on guérir d’un passé asilaire? - Wallot, Hubert (Bulletin d'histoire politique, 2002)
Keywords: Hôpital Rivière-des-Prairies; Hôpitaux psychiatriques

La découverte de la "question sociale". Sociologie et mouvements d’action jeunesse canadiens-français - Warren, Jean-Philippe (Revue d'histoire de l'Amérique française, 2002)
Keywords: Association catholique de la jeunesse canadienne-française (ACJC); Jeunesse ouvrière catholique (JOC); Sociologie

Black Media in Montreal: In Defense of Abyssinia - Williams, Dorothy (Proceedings of the Seventh Annual History in the Making Conference: History and Media, Concordia University, March 2001, 2002)
Keywords: Esclaves; Journalistes; Noirs

Differing Expectations: A Study of Chinese Children's Integration into Elementary School in Quebec - Zhongxiao, Chen (Université Concordia, 2002)
Keywords: Chinois; Enfants